Medical diagnoses among infants at entry in out‐of‐home care: A Swedish population‐register study. Issue 8 (18th July 2019) - Högberg, Ulf; Sennerstam, Roland; Wester, Knut; Högberg, Göran; Andersson, Jacob; Thiblin, Ingemar
Abstract: Background and aims: Identification of child abuse involves a medical investigation and assessment of problems related to social environment and upbringing and might necessitate out‐of‐home care. The objective of this study was to analyse infants placed in out‐of‐home care in Sweden by incidence, medical diagnoses, and perinatal factors. Methods: This was a population‐based register study of infants born in Sweden 1997 to 2014. Data were retrieved from registers at the Swedish National Board of Health and Welfare and Statistics Sweden. Outcome measures were out‐of‐home care categories: (a) "Problems Related to Social Environment/Upbringing", (b) "Abuse diagnoses without SDH (subdural haemorrhage), RH (retinal haemorrhage), rib fracture, or long bone fracture", and (c) "SDH, RH, rib fracture, or long bone fracture." As a reference population, we randomly selected infants without medical diagnoses born the same year. Results: Overall incidence of out‐of‐home care was 402 per 100 000. For subcategories (a), (b), and (c), the incidences were 14.8 (n = 273), 3.77 (n = 70), and 9.83 (n = 182) per 100 000, respectively. During the study period, the first remained unchanged; the latter two have been increasing. Compared with other reasons for out‐of‐home care, children in category (c), "SDH, RH, rib fracture, or long bone fracture", had increased odds of being boys (adjusted odds ratio [aOR] 1.60; 95% confidence interval [CI], 1.08‐2.38) and decreased odds of having a mother being single (aOR 0.49; 95% CI, 0.32‐0.75) and a smoker (aOR 0.60; 95% CI, 0.37‐0.96). Compared with the reference population, children in this category were more often twin born (7.7% versus 2.8%), preterm (18.5% versus 5.5%), and small‐for‐gestational age (5.2% versus 2.1%). Conclusion: SDH, RH, rib fracture, or long bone fracture constitute a minor part of medical diagnoses for infants entered in out‐of‐home care, but have been increasing, both in numbers and proportion. Overdiagnosis of abuse might be a possible reason but cannot be ascertained by this study design.